2018
DOI: 10.1029/2017jb015369
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Crystallization‐Induced Expansion and Creep Compaction During Gypsum Formation, and Implications for Serpentinization

Abstract: Deformation caused by reaction‐driven volume increases is an important process in many geological settings. The interaction of rocks with reactive fluids can change permeability and reactive surface area, leading to a large variety of feedbacks. Gypsum (CaSO4·2H2O) is an ideal material to study these processes. It forms rapidly at room temperature via bassanite (CaSO4·[1/2]H2O) hydration and is commonly used as an analog for rocks in high‐temperature, high‐pressure conditions. We conducted uniaxial deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
(156 reference statements)
0
21
0
Order By: Relevance
“…Completely carbonated (listvenites) and hydrated (serpentinites) peridotites are, however, frequently observed in outcrops, Reaction-driven cracking has been observed in experiments involving both carbonation of olivine (Xing et al, 2018;Zhu et al, 2016) and hydration of magnesium oxide (Zheng et al, 2018). Other experiments on analogue systems have demonstrated that hydration reactions involving lime (Lambart et al, 2018;Wolterbeek et al, 2018) and bassanite (Skarbek et al, 2018) can produce significant crystallization-induced stresses. However, the conditions under which positive feedbacks (cracking) overcome negative feedbacks (clogging) remain relatively uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Completely carbonated (listvenites) and hydrated (serpentinites) peridotites are, however, frequently observed in outcrops, Reaction-driven cracking has been observed in experiments involving both carbonation of olivine (Xing et al, 2018;Zhu et al, 2016) and hydration of magnesium oxide (Zheng et al, 2018). Other experiments on analogue systems have demonstrated that hydration reactions involving lime (Lambart et al, 2018;Wolterbeek et al, 2018) and bassanite (Skarbek et al, 2018) can produce significant crystallization-induced stresses. However, the conditions under which positive feedbacks (cracking) overcome negative feedbacks (clogging) remain relatively uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, it has been observed that the reaction rate decreases under large stress conditions (Skarbek et al, ; Wolterbeek et al, ; Zheng et al, ). Microstructural observations of Wolterbeek et al () indicated that reaction‐induced stresses shut down pathways for water into the sample, hampering ongoing reaction and limiting the magnitude of stress buildup to the values observed.…”
Section: Discrete Element Methods Model Formulationmentioning
confidence: 61%
“…The modeling of serpentinization proposed in this study provides additional information compared to previous studies (Kelemen & Hirth, 2012;Skarbek et al, 2018). In the present study, serpentinization was…”
Section: Modeling Serpentinization In Natural Conditionsmentioning
confidence: 73%
See 1 more Smart Citation
“…As a result, there is no consensus regarding the nature of deformation due to retrograde metamorphism (e.g., Ghofrani & Plack, 1993;Kuleci et al, 2017;Ostapenko & Yaroshenko, 1975;Skarbek et al, 2018;Van Noort et al, 2017;Wolterbeek et al, 2017;Zhu et al, 2016). Generation of stress due to crystallization has been mostly studied in environments where crystallization occurs within a porous medium whose matrix does not participate in the reaction.…”
Section: Introductionmentioning
confidence: 99%